Conflito, seleção estratégica e conciliação : política e democracia na ação de setores populares em Sarandi-PR - Priori, Josimar (2013)
The aim of this paper is to investigate the different configuration and patterns of collective actions taken by residents' associations in Sarandi (PR). This county is located in the metropolitan area of Maringá and it is characterized as a city marked by social inequalities and as one of the main refuge of the low-income population in the area. Throughout exploratory field, documents analyses and, above all, throughout semi-structured interviews with residents' association presidents, it is intended to comprehend the several different action plans found within voluntary associations in Sarandi, as well as its main characteristics and patterns of structured actions of different political projects. It is possible to identify that some residents' association can be included in what we call tradition of Brazilian social movements, trying to support its action by a conflictive and revendicative reason. Some other association resorted to building partnership with private relations with State agents to reach their demands. There's also another group that puts into practice what it is called strategic selection when gathering elements from different political matrix, meddling with more conflictive or conciliator elements within their activities as available strategies aiming their demands. At last, it is intended to analyze the meanings of rights, citizenship and democracy according to the residents' associations in Sarandi, as well as the implications of these agents' actions towards the democratic construction.